Evolutionary Medicine and Future of Humanity: Will Evolution Have the Final Word? - Maciej Henneberg; Arthur Saniotis (Humanities, 2013)
Evolutionary medicine in its classical form assumes that since cultural evolution is faster than biological evolution, ailments of modern people are a result of mismatch between adaptations to the past environments and current situations. A core principle is that we, humans, having evolved for millions of years in a specific natural environment (environment of evolutionary adaptation EEA) are biologically adapted to this past environment and the ancient lifestyle. This adaptation to the past produces major mismatch of our bodies with the present, highly anthropic and thus “artificial” living conditions. This article provides two areas of possible future evolution, diet and physical activity levels which have been dramatically altered in industrialised societies. Consequently, micro-evolution is an on-going process.